Inflation, Expectations and Monetary Policy: What Have We Learned and to What End? - Olivier Coibion; Yuriy Gorodnichenko (Institute of Labor Economics (IZA), 2025)
We review recent research and experiences linking inflation and expectations, emphasizing what has been learned since 2020. One clear lesson is that the inflation expectations of most economic agents have been and remain unanchored. The unanchored nature of inflation expectations, in combination with supply shocks, can explain much of the inflation surge and subsequent disinflation when viewed through the lens of an expectations-augmented Phillips curve, both in the U.S. and abroad. New policy frameworks are unlikely to address this feature of expectations. Only a communication strategy that breaks what we refer to as the "cycle of selective inattention" is likely to be successful, but it is probably already too late to stop the next inflation surge.
Keywords: E31; C83; D84; 330; communication; surveys; inflation expectations; expectations management; randomized controlled trial